Tetraphenylmethane‐Arylamine Hole‐Transporting Materials for Perovskite Solar Cells. Issue 5 (10th February 2017) - Liu, Xuepeng; Kong, Fantai; Cheng, Tai; Chen, Wangchao; Tan, Zhan'ao; Yu, Ting; Guo, Fuling; Chen, Jian; Yao, Jianxi; Dai, Songyuan
Abstract: A new class of hole‐transporting materials (HTM) containing tetraphenylmethane (TPM) core have been developed. After thermal, charge carrier mobility, and contact angle tests, it was found that TPA‐TPM (TPA: arylamine derivates side group) showed higher glass‐transition temperature and larger water‐contact angle than spiro‐OMeTAD with comparable hole mobility. Photoluminescence and impedance spectroscopy studies indicate that TPA‐TPM's hole‐extraction ability is comparable to that of spiro‐OMeTAD. SEM and AFM results suggest that TPA‐TPM has a smooth surface. When TPA‐TPM is used in mesoscopic perovskite solar cells, power conversion efficiency comparable to that of spiro‐OMeTAD is achieved. Notably, the perovskite solar cells employing TPA‐TPM show better long‐term stability than that of spiro‐OMeTAD. Moreover, TPA‐TPM can be prepared from relatively inexpensive raw materials with a facile synthetic route. The results demonstrate that TPM‐arylamines are a new class of HTMs for efficient and stable perovskite solar cells. Abstract : "Hole"efficiency : New hole‐transporting materials for perovskite solar cells are developed using tetraphenylmethane (TPM) as core and arylamine side groups (TPA and DPA). TPA‐TPM can achieve power conversion efficiency comparable to spiro‐OMeTAD as well as improved long‐term stability.